Innovation in Online Learning and Accessibility for University Students with Disabilities - Joko Yuwono; Muhammad Anwar; Erma Kumala Sari; Dewi Sri Rejeki (STAI Hubbulwathan Duri, 2022)
The aim of this study was to determine the innovation in learning and accessibility for students with disabilities in the implementation of online learning during the COVID-19 pandemic at one university in Central Java. This study is a mixed methods research using a survey approach. The respondents of this research were 20 students with disabilities. The sample was taken by purposive sampling on the basis of their participation in the Study Center of Diffability (PSD). Data collection techniques in this study were conducted through questionnaires (online form) and interviews. The online questionnaire was given to 20 disabled students at one university in Central Java. Meanwhile, the interviews were conducted with one student with visual impairment and one student with hearing impairment. The questionnaire data were analyzed using descriptive analysis techniques, while the interview data were used as additional data to support the questionnaire data. The results of the study indicate that there are still students with disabilities who experience difficulties while attending lectures at universities due to the obstacles faced, namely the lack of development of learning approach innovations to help students with disabilities to participate in the lecture process. The research conducted can run well and is expected to be useful as an effort to improve the quality of special education services in Indonesia, especially in the implementation of inclusive education services.